Employee Management During Mergers and Acquisitions: Communication Challenges and Impact on Turnover - Hasmin, Hasmin (Advances: Jurnal Ekonomi & Bisnis, 2025)
Purpose: This study explores the communication challenges involved in employee management during mergers and acquisitions (M&A) and their impact on employee turnover. It investigates how communication strategies, leadership approaches, and cultural factors influence employee engagement, trust, and retention during organizational transitions. Research Design and Methodology: A systematic literature review (SLR) approach synthesized findings from recent empirical studies and theoretical contributions related to communication management and employee retention during M&A. The study examined scholarly articles and case studies published between 2018 and 2024 to identify key themes and trends. Social Exchange Theory (SET) served as the theoretical framework to interpret the dynamics of employee-organization relationships in M&A contexts. Findings and Discussion: The findings reveal that communication barriers, such as unclear role definitions, delayed information dissemination, and inconsistent messaging, contribute to heightened employee uncertainty and turnover risks. Conversely, transparent and participatory communication, supported by empathetic leadership, fosters trust, reduces anxiety and enhances employee engagement. The study underscores the importance of involving employees in decision-making to strengthen their sense of belonging and organizational commitment. Comparisons with previous research highlight the need for an integrated communication approach that addresses structural and cultural challenges during M&A integration. Implications: This research provides practical insights for organizational leaders by recommending structured communication frameworks, leadership communication training, and implementing open feedback channels. These strategies can enhance post-merger integration, strengthen employee trust, and reduce turnover. Additionally, this study highlights the importance of further empirical research to validate findings across different organizational contexts and cultural settings.